Unveiling the impact of CD133 on cell cycle regulation in radio- and chemo-resistance of cancer stem cells - Wu, Luyao; Katsube, Takanori; Li, Xiaofei; Wang, Bing; Xie, Yi (Frontiers in Public Health, 2025)
The adaptation of malignancy to therapy presents a significant challenge in cancer treatment. The cell cycle plays a crucial role in regulating the evolution of radio- and chemo-resistance in tumor cells. Cancer stem cells (CSCs) are the primary source of therapy resistance, with CD133 being one of the most recognized and valuable cell surface markers of CSCs. Evidence increasingly suggests that CD133 is associated with cancer resistance. The current understanding of the molecular biological function of CD133 is limited, leading to ongoing debates about its role in cancer biology. In this review, we explore recent research and emerging trends related to CD133 through extensive literature and content analysis. It was summarized that new insights into the relationships of CD133 and cell cycle signaling pathways in resistant CSCs. The aim of this review is to provide a foundational understanding of how these signaling pathways and their interactions impact cancer prognosis and inform treatment strategies.